Implementation of Good Corporate Governance and Tax Planning On Company Value - Heni Agustina; Khannifah Rahmadhani; Rizqi Putri Nourma Budiarti; Rizki Amalia Elfita; Mohamad Rijal Iskandar Zhulqurnain (Jurnal Bisnis dan Keuangan, 2023)
The objective of this study to identify Good Corporate Governance and Tax Planning on Firm Value using secondary data taken from the annual financial statements of companies listed on IDX during the 2017-2020 period. The method in this study is purposive sampling, which consists of 11 companies that have been selected for sample. Independent variables in this study are managerial ownership, institutional ownership, independent board of commissioners, audit committee, tax planning. Dependent variable use in this study is firm value. The data analysis method used multiple linear regression using SPPS 25 software with a significant level of 0.05. The results of this study indicate that managerial ownership and institutional ownership have a positive effect on firm value, the board of commissioners has a negative effect on firm value, audit committees and tax planning have no effect on firm value.